The concept of disaster preparedness ini disaster-prone areas at Harapan Bahagia Yogyakarta school - Irfan Tamwifi; Eliyyil Akbar (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
This archipelago country cannot be separated from disasters which cause many victims, especially children. This affects their future lives as a generation of the nation. Children's future regarding disaster preparedness can be improved by knowing the signs and causes of disasters, what to do before and during a disaster, and survival skills. The purpose of this article is to explain the reasons why disaster preparedness education is important for young children. The method used is a qualitative descriptive method directed at field research. The results obtained are that with disaster preparedness education it is hoped that children will be far from being perceived as having limitations in dealing with disasters because proper education will bring excellence and quality of mind and clarity in thinking. Apart from that, you can also understand the nature of existing truths, and will be accustomed to carrying out good habits and actions, always behaving well, always inviting students to think carefully and deeply, always encouraging creativity and thinking about nature and living things. All forms of education will have an effective effect if given from childhood or an early age.